2021
DOI: 10.3390/ijms222111800
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Steroids-Driven Regulation of Porcine Ovarian Putative Stem Cells Favors the Onset of Their Neoplastic Transformation

Abstract: Nandrolone (Ndn) and boldenone (Bdn), the synthetic testosterone analogues with strong anabolic effects, despite being recognized as potentially carcinogenic compounds, are commonly abused by athletes and bodybuilders, which includes women, worldwide. This study tested the hypothesis that different doses of Ndn and Bdn can initiate neoplastic transformation of porcine ovarian putative stem cells (poPSCs). Immunomagnetically isolated poPSCs were expanded ex vivo in the presence of Ndn or Bdn, for 7 and 14 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 64 publications
(75 reference statements)
1
22
0
Order By: Relevance
“…Despite effective knockdown, 5.87% of embryos was able to develop into blastocysts, possibly due to the presence of maternally contributed FOLR1 which may eventually exhausted until blastocyst stage. Our results are in line with a previous study (Strandgaard et al, 2017), which demonstrated the compromised ability of mouse embryos to develop to blastocyst stage after TA B L E 1 Effect of FOLR1 knockdown on the rate of blastocyst production injection (Kharche et al, 2016;Magata et al, 2019;Menéndez-Blanco et al, 2020;Shirazi et al, 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al, 2021;Hernández Martínez et al, 2020;Samiec et al, 2019;Skrzyszowska & Samiec, 2020Wiater et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite effective knockdown, 5.87% of embryos was able to develop into blastocysts, possibly due to the presence of maternally contributed FOLR1 which may eventually exhausted until blastocyst stage. Our results are in line with a previous study (Strandgaard et al, 2017), which demonstrated the compromised ability of mouse embryos to develop to blastocyst stage after TA B L E 1 Effect of FOLR1 knockdown on the rate of blastocyst production injection (Kharche et al, 2016;Magata et al, 2019;Menéndez-Blanco et al, 2020;Shirazi et al, 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al, 2021;Hernández Martínez et al, 2020;Samiec et al, 2019;Skrzyszowska & Samiec, 2020Wiater et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The future studies at our laboratory may decipher some of these questions in order to thoroughly elucidate the importance of FOLR1 as a pivotal biomarker suitable for prediction of augmented susceptibility of embryonic genomes to efficient epigenetic reprogramming of their transcriptional activities. The latter could enable the embryologists to estimate the increased developmental competences and molecular quality of caprine and other mammalian species embryos produced by such modern assisted reproductive technologies as microsurgical IVF by intracytoplasmic sperm injection (Kharche et al., 2016; Magata et al., 2019; Menéndez‐Blanco et al., 2020; Shirazi et al., 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al., 2021; Hernández Martínez et al., 2020; Samiec et al., 2019; Skrzyszowska & Samiec, 2020, 2021; Wiater et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is beyond any doubt that, in the near future, a wide panel of the investigations from the fields of experimental and applied embryology should have been targeted at the precisely identifying and comprehensively exploring a broad spectrum of morphological, ultrastructural, biochemical, and molecular determinants responsible for increased incidence of the processes leading to initiation and progression of embryo fragmentation. The thorough characterization of the aforementioned determinants seems to be strongly justified in order to recognize the highly predictable biomarkers related to diminishments in not only molecular quality parameters, but also the extracorporeal and peri-implantation developmental capabilities of the ex vivo produced embryos created by such modern ARTs as in vitro fertilization and intracytoplasmic sperm injection in humans and other mammalian species and somatic cell nuclear transfer (SCNT)-mediated cloning in other mammalian species [114][115][116][117][118][119].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for the aforementioned reasons, the desirable OA‐mediated impacts might be reflected in the enhancements of ex vivo developmental potential, molecular quality, mitochondrial functions and incidence of genomic DNA‐inherited genes to undergo reprogramming of their transcriptional activities in porcine and other mammalian in vitro‐produced embryos that have been created using a variety of advanced assisted reproductive technologies (ARTs). Among those ARTs, special importance should be assigned to in vitro fertilization (IVF) by standard gamete co‐incubation or intracytoplasmic sperm injection (Arraztoa et al, 2017; Casillas et al, 2018; Kagawa et al, 2022; Thongkittidilok et al, 2022) and cloning by somatic cell nuclear transfer (Deng et al, 2020; Gorczyca et al, 2021; Jeong et al, 2021; Wiater et al, 2021).…”
Section: Discussionmentioning
confidence: 99%